Produksi tepung tongkol jagung muda hasil biodegradasi kapang Pleurotus ostreatus dengan enzim pemecah serat dan implikasinya pada pakan ayam pedaging - Umiani Hatta; Sugiarto Sugiarto (Faculty of Animal Science, Universitas Brawijaya, 2015)
The purpose of this study was to determine young maize stover flour production resulted from biodegradation Pleurotus ostreatus fungi with fiber digesting enzyme on broiler feed implications. Materials used in this research were young maize stover (60-70 days), Pleurotus ostreatus fungi, urea (CO-(NH2)2), readily available carbohydrate, aquadest and alcohol. The method used ANOVA test with five treatments and four replication: R0 = control (without fermentation), R1 = 10g Pleurotus ostreatus/kg TTJM; R2 = 20g Pleurotus ostreatus/kg TTJM; R3 = 20g Pleurotus ostreatus/kg TTJM and R4 = 40g Pleurotus ostreatus/kg TTJM. The result showed best effect of crude protein R2= 32.33, best effect of crude fat R4= 18.59, best effect of crude fiber RO= 119.70, and best effect of energy (kkal) R4= 20682.59. The study concluded that the increasing crude protein and crude fat also decreased crude fiber content as a result of fermentation using Pleurotus ostreatus. The energy content of maize stover had no significant effect due to fermentation. Key words : fermentation, enzyme, maize stover, broiler